Nonhuman Primate Infections after Organ Transplantation - Haustein, Silke V. (ILAR J, 2008)
Nonhuman primates, primarily rhesus macaques (Macaca mulatta), cynomolgus macaques (Macaca fascicularis), and baboons (Papio spp.), have been used extensively in research models of solid organ transplantation, mainly because the nonhuman primate (NHP) immune system closely resembles that of the human. Nonhuman primates are also frequently the model of choice for preclinical testing of new immunosuppressive strategies. But the management of post-transplant nonhuman primates is complex, because it often involves multiple immunosuppressive agents, many of which are new and have unknown effects. Additionally, the resulting immunosuppression carries a risk of infectious complications, which are challenging to diagnose. Last, because of the natural tendency of animals to hide signs of weakness, infectious complications may not be obvious until the animal becomes severely ill. For these reasons the diagnosis of infectious complications is difficult among post-transplant NHPs. Because most nonhuman primate studies in organ transplantation are quite small, there are only a few published reports concerning infections after transplantation in nonhuman primates. Based on our survey of these reports, the incidence of infection in NHP transplant models is 14%. The majority of reports suggest that many of these infections are due to reactivation of viruses endemic to the primate species, such as cytomegalovirus (CMV), polyomavirus, and Epstein-Barr virus (EBV)–related infections. In this review, we address the epidemiology, pathogenesis, role of prophylaxis, clinical presentation, and treatment of infectious complications after solid organ transplantation in nonhuman primates.